Bond's top 100 franchises (Source Book, 2006)
Bond's Top 100 Franchises features detailed analyses of the best franchises picked from the more than 2,300 available and consolidates and updates the individual profiles originally printed in Robert Bond's acclaimed Top 50 Franchises series. The final selection is based on a number of factors, including historical performance, competitive advantage, franchisee satisfaction, and financial stability. Drawing on the author's 15 years' experience in this field, Bond's Top 100 Franchises offers detailed analyses of those franchise opportunities that have proven to be the best investments available to the general investor.